Strategic Planning Using Engaged Scholarship: Building A Reentry Organization - Watson, Jerry (Advances in Social Sciences Research Journal, 2022)
Given the incredible growth in incarceration numbers and resultant increases in returning prisoners, reentry programs play a critical role in the lives of justice involved individuals and their families, and communities. The aim of this engaged scholarship effort was to work in partnership with a community-based reentry organization to conduct strategic planning. Among the unique organizational assets identified were mental health services, social support groups, clinical professional development, and social entrepreneurship including housing and innovative technology development initiatives. Building on Indomitable Families Affected by Incarceration’s history, strengths, and opportunities, the results yielded a set of action steps to guide the organization’s future.